(untitled) (Baghdad Science Journal, 2016)
In this work, a series of new Nucleoside analogues (D-galactopyranose linked to oxepanebenzimidazole moiety) was synthesized via multisteps synthesis. The first step involved preparation of two benzimidazoles 2-styrylbenzimidazole and 2-(phenyl ethynyl) benzimidazole via reaction of phenylenediamine with cinnamic acid or ?-phenyl propiolic acid. Electrophilic addition of the prepared benzimidazoles by three anhydrides in the second step afforded (4-6) and (14-16) which in turn were treated with 1,2,3,4-di-O-isopropylidene galactopyranose in the third step to afford a series of the desirable protected nucleoside analogues (7-9) ,(17-19)which after hydrolysis in methanolic sodium methoxidein the fourth step afforded the free nucleoside analogues (10-12) and (20-22) .The synthesized compounds were identified by FT-IR and some of them by 1H-NMR and13C-NMR. The synthesized oxepane nucleoside analogues were screened for their antibacterial activity against three types of bacteria including Staphylococcusaureus ,Bacillus(gram positive) andE.coli (gram negative) bacteria repectively.